Jovan Grčić and German Literature - Pasula, Milica B. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
Jovan Grčić (1855–1941) was an exceptional expert on German language and culture and one of the most prominent Serbian intellectuals from around the turn of the 20th century. However, his translations were forgotten in the following decades and are completely unknown to contemporary readers and academics. The aim of this paper is to call attention to Grčićʾs essential contribution to the field of German and Serbian cross-cultural connections, as well as to highlight and analyze the most significant elements of his translational poetics. This paper presents the extent to which the influence of the target culture is represented in his translations. It focuses on the unpublished translations of two crucial dramatic works: Goetheʾs Die Geschwister and Schillerʾs Die Braut von Messina. The main characteristics of Grčićʾs translational style are analyzed, which include: his adaptation of original texts in the target culture, the transfer of proper names into Serbian, and the modification of structural and formal elements of original texts as well as deviations relating to their content. The analysis shows that Grčićʾs translational poetics is a product of cultural and historical context as well as his admirable knowledge of German and his gifted approach to his mother tongue, which are represented in the poetical quality of his work.